MOTHER'S KNOWLEDGE RELATIONSHIP WITH GIVING EXCLUSIVE ASI IN THE WORKING AREA OF UPT PUSKESMAS MERAL KARIMUN DISTRICT RIAU ISLANDS PROVINCE - Ade Ricky Harahap; Acholder Tahi Perdoman (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2020)
Background : Based on the Riau Islands Province Health Profile in 2016, exclusive breastfeeding shows an increase but is still far below the national target (80%) and still low compared to the national achievement (54%). The trend of exclusive breastfeeding coverage in Riau Islands Province from 2014 was 31.74%, 2015 was 41.70% and 2016 was 41.91%. The research objective was to determine the relationship between maternal knowledge and exclusive breastfeeding. Method : Research method This research is a research in the form of an analytic survey with a cross sectional study design. The method used is quota sampling and obtained 79 respondents as a sample. Data collection using a questionnaire. Result : The analysis of the relationship between knowledge of respondents and exclusive breastfeeding showed that of the 11 respondents who had low knowledge about exclusive breastfeeding, 11 respondents (13.9%) did not provide exclusive breastfeeding and there were no respondents who provided exclusive breastfeeding (0%), whereas Of the 68 respondents who have high knowledge, 37 respondents (46.8%) do not provide exclusive breastfeeding and 31 respondents (39.2%) provide exclusive breastfeeding. Based on the results of the chi square statistical test, it was obtained p = 0.004, which means that the p value was less than 0.05 (0.004 <0.05).